Transforming Early Childhood Education: A Cutting-Edge Online Platform to Enhance English Skills and Qur'anic Recitation - Mira Shodiqoh; Ela Rosyida (Alzam: Journal of Islamic Early Childhood Education, 2026)
This study explores the role of an innovative online learning platform in enhancing English language skills and Qur’anic recitation among early childhood learners using a qualitative approach. It focuses on understanding children’s learning experiences, engagement patterns, and the perspectives of parents and educators regarding the integration of digital technology. Data were collected through participant observation, semi-structured interviews, and documentation. The findings reveal that interactive multimedia-based platforms effectively increase children’s engagement and support the development of basic English vocabulary and accurate Qur’anic pronunciation. Audio-visual features, repetition, and gamification help maintain attention and motivation, while parental involvement and teacher guidance play a crucial role in optimizing learning outcomes. This study highlights the importance of designing age-appropriate and integrative platforms that combine linguistic and religious learning.